Actaplanin: A new growth promoter for broilers - ΤΣΑΛΤΑΣ, Κ.; ΚΥΡΙΑΚΗΣ, Σ.; ΑΝΔΡΕΩΤΗΣ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
Actaplanin is a glycopeptide antibiotic produced by a strain of Aciinoplanes missouriensis. To assess the efficacy of actaplanin as a growth promoter for broilers, the drug was fed at concentrations of 0, 5, 10, 15, 20 and 40 ppm in 8 floor pen trials in Greece, where a total of 9,440 Hubbard broilers were tested. Monensin was used as an anticoccidial agent in all trials at a concentration of 100 ppm. No adverse reactions attributable to treatments were observed in any of the eight trials. The overall average total mortality for the above treatments was 3.63, 3.38, 3.20, 2.83, 2.90 and 3.14% respectively. Average liveweights per bird at trial termination (49 days) for birds medicated with the above treatments were 1491, 1506, 1548, 1539, 1544 and 1525 g respectively; while overall feed gain rations were 2.210, 2.177, 2.171, 2.154, 2.157 and 2.154 respectively. Overall pooled statistical analysis of the results of these trials revealed that mortality was not affected by any concentration of the drug and that all actaplanin treatments produced significant improvements in weight gains and feed/gain ratios when compared to non-medicated controls. The results therefore support the effectiveness of actaplanin as a growth promoter for broilers